Single-dose methotrexate for ectopic pregnancy treatment: preliminary data - Merisio, C.; Anfuso, S.; Berretta, et al., R. (Acta Biomedica Atenei Parmensis, 2005)
Background and aim of the work: our purpose was to evaluate the efficacy of a single-dose of MTX for ectopic pregnancy treatment in a sample of patients carefully selected according to strict inclusion criteria. Methods: 11 patients that matched the inclusion criteria were enrolled. Results: β-hCG at diagnosis averaged 1349 mIU/ml out of the 11 treated patients, 10 (90%) received a single dose of MTX and had a time of EP resolution averaging 27,3 days. The remaining patient received an additional dose of MTX, equal to the start dose, with a time resolution of 35 days. Conclusions: This study provides evidence of the efficacy of MTX in EP treatment, both as therapy and as a form of clinical management: the successful medical management of EP, defined as β-hCG levels becoming negative after administration of one or more MTX doses, was obtained in all treated cases.